RESEARCH OF TECHNOLOGICAL EFFICIENCY OF HARBEL PEELING AND ITS INFLUENCE QUALITY OF FOOD - Baltabaev Ulugbek Narbaevich; Boymuhammedov Muhammadali; Abdullaeva Feruza (Journals Park Publishing, 2022)
Experimental data by definition of technological efficiency clearing and offered peeling machinery for peeling of the grain of barley, the maintenance of beaten grains before and after peeling, quality indicators of mixed fodders have resulted. Thus, after application offered peeling machinery the quantity of the whole kernel increases to 8%, beaten grain decreases by 3%, and cellulose for 3.5% and by that leads to forage mastering, improvement of the digestion of animals and quality indicators of mixed sats.
Keywords: barley; flaking; fiber